The Mediating Role of Work-Family Conflict on the Effects of Workload - Mohd Shamsuri Md Saad, Siswoyo Haryono, Hanifah Nur’Aini, (Opción, 2019)
This study is motivated by the phenomenon of high turnover in pharmaceutical companies. This paper aimed to analyze the effects of workload, work family conflict, and work stress on turnover intention. Besides, the mediating role of work family conflict and work stress on the effect of workload on turnover intention were also analyzed. The results showed that workload had a positive and significant effect on turnover intention, work family conflic and work stress. Work family conflict and work stress had no significant impact on workload on turnover intention.